1997
DOI: 10.1016/s0020-7292(96)02830-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated second trimester human chorionic gonadotropin level associated withadverse pregnancy outcome

Abstract: Unexplained elevation of human chorionic gonadotropin in the second trimester appears to be associated with adverse pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 18 publications
3
32
1
Order By: Relevance
“…Our results are consistent with that of Vidyabati et al and Gonen et al who conducted a prospective cohort study on pregnant patients and found that women with elevated levels of beta HCG had a significantly higher risk of hypertension. 4,15 Observations made in present study were also consistent with those of Sorensen et al, Wenstrom et al, Benn et al, Yang et al and Onderoglu et al 5,6,[16][17][18] The above association could be explained by the early placental vascular damage in preeclamptic women leading to decreased oxygen supply, which might result in increased HCG production by the hyperplastic syncytotrophoblastic cells.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with that of Vidyabati et al and Gonen et al who conducted a prospective cohort study on pregnant patients and found that women with elevated levels of beta HCG had a significantly higher risk of hypertension. 4,15 Observations made in present study were also consistent with those of Sorensen et al, Wenstrom et al, Benn et al, Yang et al and Onderoglu et al 5,6,[16][17][18] The above association could be explained by the early placental vascular damage in preeclamptic women leading to decreased oxygen supply, which might result in increased HCG production by the hyperplastic syncytotrophoblastic cells.…”
Section: Discussionsupporting
confidence: 91%
“…An association has been reported between preeclampsia and elevated third trimester hCG levels 2 . Considerable evidence suggests an association between serum hCG levels and preclampsia [7][8][9][10][11][12] . Physiological concentrations of hCG is significantly increased in vitro capillary formation and migration of endothelial cells in a dosedependant manner and has a novel function in ueterine adaptation to early pregnancy 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This observation takes on an added significance because of reports that certain pregnancy disorders (e.g. Down syndrome, pre-eclampsia, early pregnancy loss) are characterized by abnormal hCG levels (Bogart et al 1987, Heinonen et al 1996, Hurley et al 1996, O'Leary et al 1996, Onderoglu & Kabukcu 1997, Haddow et al 1998. We have evidence that pregnancies which will not carry to term have an easily recognized difference in production of hCG isoforms (O'Connor et al 1998).…”
Section: Introductionmentioning
confidence: 87%